Pengaruh Relaksasi Otot Progresif Terhadap Pola Tidur Pada Lansia di Dusun Daleman Desa PorehKecamatan Lenteng - Hidayat, Syaifurrahman; hanifah, Millatul (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2018)
Sleep is an important aspect for maintaining a healthy body. This study aims to determine the effect of progressive muscle relaxation on sleep patterns in the elderly in Daleman Hamlet Poreh Village Lenteng District. Research design pre experiment use one group pre-post test design.The population in this study is elderly in Dusun Daleman Village Poreh Lenteng District as many as 103 people with a sample of 30 people. The sampling technique used is proporsive sampling. Using statistical tests Wilcoxon with Î± 0,05.The result of the research before progressive muscle relaxation in elderly mostly experienced bad sleep pattern asmuch as (63%) that is 19 people, then after progressive muscle relaxation there was improvement of good sleep pattern as much as 60% that is 18 people.TheÂ result of data analysis using Wilcoxon test obtained p = 0,000 (<0,05) which mean there is influence of progressive muscle relaxation to sleep pattern at elderly in Daleman hamlet Porah Village Lenteng Subdistrict.Progressive muscle relaxation may be used in the elderly especially those experiencing poor sleep patterns, as progressive muscle relaxation may facilitate sleep can also be usefulfor anxiety, reduce fatigue, muscle cramps and neck and back pain so as to improve comfort during sleep.Keywords: Progressive Muscle, Sleep Pattern, Elderly